2018
DOI: 10.1017/ice.2018.183
|View full text |Cite
|
Sign up to set email alerts
|

The preventable proportion of healthcare-associated infections 2005–2016: Systematic review and meta-analysis

Abstract: ObjectiveThe preventable proportion of healthcare-associated infections (HAIs) may decrease over time as standards of care improve. We aimed to assess the proportion of HAIs prevented by multifaceted infection control interventions in different economic settings.MethodsIn this systematic review and meta-analysis, we searched OVID Medline, EMBASE, CINAHL, PubMed, and The Cochrane Library for studies published between 2005 and 2016 assessing multifaceted interventions to reduce catheter-associated urinary tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
136
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(151 citation statements)
references
References 38 publications
1
136
1
13
Order By: Relevance
“…Although HAIs are a significant challenge for healthcare systems, it is believed that more than 30% of HAIs could be prevented by correct IPC measures [6,20]. Unfortunately, adherence to best practices and guidelines is very low [10,21].…”
Section: Outcome and Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HAIs are a significant challenge for healthcare systems, it is believed that more than 30% of HAIs could be prevented by correct IPC measures [6,20]. Unfortunately, adherence to best practices and guidelines is very low [10,21].…”
Section: Outcome and Impactsmentioning
confidence: 99%
“…The global HAI prevalence has been reported to be up to 15.5% in low and middle income countries, and the number is growing [1][2][3][4][5]. On the other hand, 35 to 55% of HAIs can be reduced by applying multimodal infection control measures [6].…”
Section: Introductionmentioning
confidence: 99%
“…The International Nosocomial Infection Control Consortium stated in 2008 that not only is the risk of healthcare-associated infections (HAI) higher in developing countries, but also its impact on patients and health systems [6]. A systematic review has shown that 35-55% of HAI are preventable [7].…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which HAIs can be prevented remains largely debatable. Several reviews suggest that up to 70% of HAIs are potentially preventable (Umscheid et al, 2011, Schreiber et al, 2018. With improvements in infection prevention and reductions in infection rates, the proportion of potentially preventable HAIs continues to decrease, resulting in an infection prevention law of diminishing returns (Schreiber et al, 2018).…”
mentioning
confidence: 99%
“…Several reviews suggest that up to 70% of HAIs are potentially preventable (Umscheid et al, 2011, Schreiber et al, 2018. With improvements in infection prevention and reductions in infection rates, the proportion of potentially preventable HAIs continues to decrease, resulting in an infection prevention law of diminishing returns (Schreiber et al, 2018). As the principle tenet of medicine is first do no harm, infection prevention programs should relentlessly pursue reliable, sustainable, and practical strategies for heightened patient safety (Bearman et al, 2019).…”
mentioning
confidence: 99%